ANALISIS PERBANDINGAN TEBAL LAPIS TAMBAH. ANTARA METODE PDT-05-2005 B DENGAN METODE AASHTO 1993: (Studi Kasus : Ruas Jalan Brigjen Wasita Kusuma) - rozy, fahrul; Saepudin, Uu; Martha, Taufik (Jurnal Ilmiah Teknik Sipil, 2026)
In general, the road pavement construction commonly used in Indonesia is flexible pavement. Flexible pavement is a pavement that uses asphalt as a binding material consisting of layers placed on top of compacted subgrade. However, on the Brigjen Wasita Kusuma Road Section in Tasikmalaya City, damage occurs in the form of cracks, peeling, and obesity which reduces the comfort and service life of the road. To overcome these problems, proper overlay thickness planning is required. This study aims to analyze and compare the results of overlay thickness planning using the PDT-05-2005-B and AASHTO 1993 methods on this road section. The data used include primary data in the form of Average Daily Traffic (LHR) and secondary data in the form of subgrade CBR values, deflection data, climate, and existing pavement conditions. The analysis results show significant differences between the two methods. The PDT-05-2005-B method produces an overburden thickness requirement of 7.83 cm (rounded to 8 cm), while the AASHTO 1993 method produces an overburden thickness of 19 cm. This difference is due to differences in the calculation basis: the PDT-05-2005-B method is based on local Indonesian conditions (climate, materials, traffic, and national technical standards), while the AASHTO 1993 method uses an international approach based on structure number (SN), drainage factor, and axle load equivalent tables. From the comparison results, the PDT-05-2005-B method is considered more optimal for use in field conditions in Indonesia because the results are more realistic, economical, easy to apply, and able to minimize the risk of premature damage such as reflective cracks and plastic deformation.